Effect of the New Science Philosophy on The Urban Design of Neo Realist and Neo Rationalism - AL ANI, M. K. (Nahrain University College of Engineering Journal, 2008)
There are many intellectual thesis emerge in philosophy of science, which interest with unity and integration between sciences, and their effect on the other fields of knowledge. This direction changes the old vision about rupture between sciences. We can see this rupture by western philosophers in the Rationalism and Empiricism knowledge in spit of the intellectual thesis of Moslem philosophers about the unity of science fields so as we can there are effects of the newscience philosophers on the urban designers works in the Post Modern Architecture ( Neo Realist & Neo Rationalism ). Carl Popper & Thomas Kuhn submit new concepts in the new science philosophy, we can see their reflection on the works of the urban designers in the Neo Realist ( Geoffrey Broadbent & Bill Hillier ) and Neo Rationalism ( Aldo Rossi & Leo Rob Krier ). The research deals with their intellectual thesis to determine their reflection on the urban designprojects.